Pain After Unilateral Total Knee Arthroplasty: A Prospective Randomized Controlled Trial Examining the Analgesic Effectiveness of a Combined Adductor Canal Peripheral Nerve Block with Periarticular Infiltration Versus Adductor Canal Nerve Block Alone Versus Periarticular Infiltration Alone. (June 2016) - Sawhney, Monakshi; Mehdian, Hossein; Kashin, Brian; Ip, Gregory; Bent, Maurice; Choy, Joyce; McPherson, Mark; Bowry, Richard
Abstract : BACKGROUND: Total knee arthroplasty is a painful surgery that requires early mobilization for successful joint function. Multimodal analgesia, including spinal analgesia, nerve blocks, periarticular infiltration (PI), opioids, and coanalgesics, has been shown to effectively manage postoperative pain. Both adductor canal (AC) and PI have been shown to manage pain without significantly impairing motor function. However, it is unclear which technique is most effective. This 3-arm trial examined the effect of AC block with PI (AC + PI) versus AC block only (AC) versus PI only (PI). The primary outcome was pain on walking at postoperative day (POD) 1. METHODS: One hundred fifty-one patients undergoing unilateral total knee arthroplasty were included. Patients received either AC block with 30 mL of 0.5% ropivacaine or sham block. PI was performed intraoperatively with a 110-mL normal saline solution containing 300 mg ropivacaine, 10 mg morphine, and 30 mg ketorolac. Those patients randomly assigned to AC only received normal saline knee infiltration. RESULTS: On POD 1, participants who received AC + PI reported significantly lower pain numeric rating scale scores on walking (3.3) compared with those who received AC (6.2) or PI (4.9) ( P < 0.0001). Participants who received AC reported significantly higher pain scores at rest and knee bend compared with those who received AC + PI or PI ( P < 0.0001). The difference in pain scores between participants who received AC + PI and those who received AC was 2.83 (95% confidence interval, 1.58–4.09) and the difference between those who received AC + PI and those who received PI was 1.61 (95% confidence interval, 0.37–2.86). On POD 2, participants who received AC + PI reported significantly less pain on walking (4.4) compared with those who received AC (5.6) or PI (5.6) ( P = 0.006). On POD 2, there was no difference between the groups for pain at rest or knee bending. Participants who received AC used more IV patient-controlled analgesia on POD 0. There was no difference between the groups regarding distance walked. CONCLUSIONS: Participants who received AC + PI reported significantly less pain on walking on PODs 1 and 2 compared with those who received AC only or PI only. Abstract : Published ahead of print March 29, 2016